2005
DOI: 10.1097/01.pas.0000168177.71405.ac
|View full text |Cite
|
Sign up to set email alerts
|

Peribronchiolar Metaplasia: A Common Histologic Lesion in Diffuse Lung Disease and a Rare Cause of Interstitial Lung Disease

Abstract: Peribronchiolar metaplasia (PBM) is a histologic lesion consisting of peribronchiolar metaplasia (PBM) of bronchiolar-type epithelium. Although widely recognized, PBM has received little attention in the pathologic literature and is not known to have clinical significance. We identified 15 cases in which PBM was the only major histologic finding in surgical lung biopsies from patients with interstitial lung disease (PBM-ILD), and we reviewed the clinical, imaging, and pathologic findings. The mean age was 57 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 11 publications
4
81
1
3
Order By: Relevance
“…No CT imaging data were available. In contrast to isolated PBM, which generally appears to be innocuous, 34 3 of 9 patients (33%) with bronchiolocentric interstitial pneumonia and follow-up died of disease, and 5 others were alive with progressive disease. Yousem and Dacic 40 speculated that this process might be a form of CHP, but none of the cases had any obvious antigen exposures.…”
Section: Other Possible Morphologic Variants Of Chp: Idiopathic Broncmentioning
confidence: 94%
See 1 more Smart Citation
“…No CT imaging data were available. In contrast to isolated PBM, which generally appears to be innocuous, 34 3 of 9 patients (33%) with bronchiolocentric interstitial pneumonia and follow-up died of disease, and 5 others were alive with progressive disease. Yousem and Dacic 40 speculated that this process might be a form of CHP, but none of the cases had any obvious antigen exposures.…”
Section: Other Possible Morphologic Variants Of Chp: Idiopathic Broncmentioning
confidence: 94%
“…Moreover, PBM can be found in otherwise healthy lungs but is particularly frequently found in lungs with any kind of fibrosing interstitial pneumonias. Fukuoka et al 34 reported PBM in 17 of 29 UIP cases (59%), 10 of 20 NSIP cases (50%), 3 of 6 desquamative interstitial pneumonia cases (50%), 9 of 18 HP cases (50%), and 2 of 18 respiratory bronchiolitis with interstitial lung disease cases (11%). Myers and colleagues 29,35 concluded that PBM was present in 50% of HP biopsies and in 100% of HP autopsies but noted that the frequency of PBM was similarly high in UIP/IPF biopsies, so that it was not diagnostically useful in that context.…”
Section: Peribronchiolar Metaplasiamentioning
confidence: 99%
“…Peribronchiolar lymphoid aggregates may be present and were seen in 79% of surgical lung biopsies reported by Trahan et al 37 Fibrosis of peribronchiolar interstitium may accompany the lymphocytic infiltrate and include hyperplasia of bronchiolar-type epithelium, a combination of histologic findings for which the term PBM has been proposed. 48 Peribronchiolar metaplasia is not specific, however, and may be seen in other conditions including UIP, NSIP, desquamative interstitial pneumonia, and a unique form of diffuse fibrotic airway disease termed PBM-interstitial lung disease or airway-centered interstitial fibrosis. 48,49 Peribronchiolar metaplasia is universal at autopsy in patients with chronic hypersensitivity pneumonia, but is also seen in nearly three-fourths of patients with UIP.…”
Section: Commentmentioning
confidence: 99%
“…48 Peribronchiolar metaplasia is not specific, however, and may be seen in other conditions including UIP, NSIP, desquamative interstitial pneumonia, and a unique form of diffuse fibrotic airway disease termed PBM-interstitial lung disease or airway-centered interstitial fibrosis. 48,49 Peribronchiolar metaplasia is universal at autopsy in patients with chronic hypersensitivity pneumonia, but is also seen in nearly three-fourths of patients with UIP. 50 Other evidence of the bronchiolocentric nature of hypersensitivity pneumonia may include organizing pneumonia, referred to historically as bronchiolitis obliterans organizing pneumonia, which is present in as many as half of cases.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation